Relación Entre La Sensibilidad Al Premio Y Al Castigo Y Los Niveles Motivacionales. Estudiantes Superiores De Música, Instrumentistas De Viento Metal - Francisco Javier Zarza-Alzugaray (European Scientific Journal, ESJ, 2018)
The sensitivity to reward and punishment, within the theory of anxiety of Gray (1986) is considered as one of the ways to explain different motivational aspects and activators or inhibitors of behavior. In this sense, in this article we present how from the two activation or inhibition of behavior ways we can see how the motivation of a sample of students of higher level wind instruments is modulated and explained. Thus, the specific demands of task related together with the sensitivity to punishment are the factors that have the greatest explanatory and associative power, while factors such as sensitivity to punishment or perfectionism need further study to clarify their role in the explanation of the general motivation and of the presence of behavior activation. Finally, a better knowledge of these constructs will allow the educational community to improve the teaching practice.